Securing financial independence in the legal basis of a central bank (The Capital Needs of Central Banks, 2011)
The 1990s saw much economic and legal discussion of central bank independence, often inspired by the creation of the European System of Central Banks (ESCB) and the European Central Bank (ECB), and the related institutional reforms in a number of European Union countries. But the topic remains on the agenda, and not only for academics. Many but certainly not all countries have accepted and implemented the philosophy underlying central bank independence. Moreover, even if the rationale behind operational independence for the central bank is recognized, the implications for the concrete legal arrangements remain a subject of debate. In a democratic society central bank independence needs to be counterbalanced by mechanisms ensuring the accountability of the central bank for the performance of the tasks with which it is entrusted. Furthermore, many of the aspects of the debate on central bank independence and accountability are being revisited in the context of discussions about the position of financial regulatory agencies vis-à-vis government.1